ANALYSIS OF THE EFFECT OF FINANCIAL PERFORMANCE ON STOCK PRICE AT HIMBARA BANKS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2017-2021 PERIOD - Jayanti, Richa (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2023)
This study aims to analyze the effect of financial performance proxied by the variables Capital Adequacy Ratio (CAR), Return On Equity (ROE), and Loan to Debt Ratio (LDR) on stock prices at Himbara banks listed on the Indonesia Stock Exchange for the 2017-2021 period. The population in this study are himbara banks listed on the Indonesia Stock Exchange for the 2017-2021 period. The samples in this study were 4 banks obtained by sampling technique using the purposive sampling method. Collecting data in this research uses secondary data collection, namely quantitative data. The results of the analysis in this study indicate that the variables Capital Adequacy Ratio (CAR), Return On Equity (ROE), and Loan to Debt Ratio (LDR) partially have no positive and significant effect on stock prices. Capital Adequacy Ratio (CAR), Return On Equity (ROE), and Loan to Deposit Ratio (LDR) simultaneously affect stock prices. The results of the Coefficient of Determination (R2) show that the variables Capital Adequacy Ratio (CAR), Return On Equity (ROE), and Loan to Debt Ratio (LDR) have an effect of 18.5% on stock prices. While the remaining 81.5% is influenced by other factors not discussed in this study.